Answer:
Answer
Did u put any picture because i think there should be a picture
Answer:
x
=
ln
(
3
)
7
ln
(
3
)
+
ln
(
7
)
Step-by-step explanation:
Answer:
Yes, (-3, -9) is a solution.
Step-by-step explanation:
y = 3x (-3,-9)
-9 = 3(-3)
-9 = -9
Answer:
![6](https://tex.z-dn.net/?f=6)
Step-by-step explanation:
Given: ![y=-2x+6](https://tex.z-dn.net/?f=y%3D-2x%2B6)
Since the equation is written in slope-intercept form, it is extremely easy to find the y-intercept. Slope-intercept form is written as:
![y=mx+b](https://tex.z-dn.net/?f=y%3Dmx%2Bb)
Whereas:
y: range
m: slope
x: domain
b: y-intercept
With that in mind, we can immediately tell that 6 is the y-intercept.